2021
DOI: 10.1101/2021.02.18.431829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and tissue localization of zebrafish homologs of the humanABCB1multidrug transporter

Abstract: Given its similarities with mammalian systems, the zebrafish has emerged as a potential model to study the blood-brain barrier (BBB). Capillary endothelial cells at the human BBB express high levels of P-glycoprotein (P-gp, encoded by the ABCB1 gene) and ABCG2 (encoded by the ABCG2 gene). However, little information has been available about ATP-binding cassette transporters expressed at the zebrafish BBB. In this study, we focus on the characterization and tissue localization of two genes that are similar to h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Amino acid sequence comparison between Ta-ABCB1 and vertebrate ABCB1 orthologs (Fig. 1, inserts) shows 74% sequence identity to ABCB4 of model fish species D. rerio and only 53% sequence identity to D. rerio ABCB5, the two identified P-glycoproteins in zebrafish (Fischer et al, 2013;Gordon et al, 2019;Robey et al, 2021). Interestingly Southern Platyfish (X. maculatus) ABCB1/4 had 80.1% sequence identity to Ta-ABCB1.…”
Section: Phylogenetic Analysis Of Ta-abcb1mentioning
confidence: 99%
“…Amino acid sequence comparison between Ta-ABCB1 and vertebrate ABCB1 orthologs (Fig. 1, inserts) shows 74% sequence identity to ABCB4 of model fish species D. rerio and only 53% sequence identity to D. rerio ABCB5, the two identified P-glycoproteins in zebrafish (Fischer et al, 2013;Gordon et al, 2019;Robey et al, 2021). Interestingly Southern Platyfish (X. maculatus) ABCB1/4 had 80.1% sequence identity to Ta-ABCB1.…”
Section: Phylogenetic Analysis Of Ta-abcb1mentioning
confidence: 99%
“…In preliminary studies with HEK293 cells transfected with empty vector (Vector), or with vectors encoding human ABCG2 (R5), zebrafish abcg2a (ZF Abcg2a), zebrafish abcg2b (ZF Abcg2b), zebrafish abcg2c (ZF Abcg2c), or zebrafish abcg2d (ZF Abcg2d), we noted very different substrate specificities in the zebrafish homologs as compared to human ABCG2. As shown in Figure 4, all of the zebrafish forms conferred similar levels of resistance to the known ABCG2 substrates THZ531, THZ1 [83] , and gedatolisib [81] . However, stark differences were noted for mitoxantrone, SN-38 and topotecan, as only Abcg2a and Abcg2d conferred appreciable resistance to mitoxantrone or SN-38, and none of the zebrafish homologs conferred resistance to topotecan.…”
Section: Potential Problems With the Zebrafish Modelmentioning
confidence: 99%
“…Since these results pointed to a difference in substrate specificity between the zebrafish homologs, we performed a high-throughput screen on the transfected cells using 90 substrates of P-gp [ 81 ] . By comparing the drug response area under the curve for cells transfected with empty vector and the different transporters, we found that the substrate specificity profile of zebrafish Abcb4 is similar to that of human P-gp [ 82 ] . Additionally, we found that the efficacy of human P-gp inhibitors varied for zebrafish Abcb4 and Abcb5 and depended on the substrate examined.…”
Section: The Zebrafish As a Model To Study Abc Transporters At The Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish Abcb5 has a different function than the mammalian protein. It is another apical solute transporter related to xenobiotic efflux ( Kropf et al, 2020 ; Robey et al, 2021 ). The zebrafish bile acid cyprinol sulfate induces the transcription of abcb5 in zebrafish liver ( Reschly et al, 2007 ), suggesting potential roles of Abcb5 related to biliary excretion.…”
Section: Abc Proteinsmentioning
confidence: 99%